Hotel website dimensions – analyzing international tourists’ intention to purchase online / Azdel Abdul Aziz - Abdul Aziz, Azdel (2010)
Internet has become the major distribution channel of hotel industry. Hotel in Malaysia have started to implement this type of distribution channel to their organization. One of the tools that can introduce the hotel globally and being a medium to interact with the customers is by using hotel website. Therefore, hotel website needs to be effective so that it meets the preferences of the tourist. This study is to investigate the hotel website dimensions to be considered in relation with the international tourists’ intention to purchase online. The hotel website dimensions will be measured by two categories of variable which are website interactivity (Stepchenkova et al., 2009) and website information (Rong et al., 2009). Sample of 400 foreign tourists at Kuala Lumpur International Airport were selected. This research analyzed the relationship of these dimensions and the intention to purchase online by the international tourists. The most important dimension that attracts online purchasing also been selected throughout the study. The results show that there were positive relationship between each hotel website dimensions and online purchase intention. The study also concluded that website information was the most important variables in hotel website dimension. Practically, this research has shown the importance of understanding in choosing the best and appropriate website dimension to encourage customer to purchase via online.